Pulmonary and Peritoneal Tuberculosis Associated with Tumor Necrosis Factor-Alpha Inhibitor Use: A Case Report and Review of the Literature. (4th December 2012) - Tipirneni, Niharika; Siegel, Marc O.
Abstract : The association between the use of tumor necrosis factor- α inhibitors and the increased risk of granulomatous infections, especially tuberculosis, has been well documented. Given the rapidly expanding list of inflammatory conditions for which tumor necrosis factor- α inhibitors are receiving FDA approval, the incidence of tuberculosis in this patient population has increased. Despite heightened awareness by physicians, the diagnosis of tuberculosis can remain challenging, given that extrapulmonary sites of infection are more frequently involved. We present a case of pulmonary and peritoneal tuberculosis in a gentleman being treated with a tumor necrosis factor- α inhibitor and discuss the diagnostic challenges of establishing the diagnosis.